PENGARUH TAX AVOIDANCE TERHADAP COST OF DEBT PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS PEFINDO 25 - Dwi Septa Aryani; Kusminaini Armin (Jurnal RATRI (Riset Akuntansi Tridinanti), 2022)
This study aims to determine the effect of the tax avoidance on the cost of debt in Pefindo 25 index. The sampel in this study were all companies list in pefindo 25 index for the 2019- 2021 period. The analysis technique used in this research is a simple regression analysis.The results showed that tax avoidance had positive effect on the cost of debt. Keyword : Tax Avoidance and  Cost of Debt